ANALISIS EFISIENSI KINERJA PERUSAHAAN MELALUI PENDEKATAN SISTEM DU PONT PADA PT HM SAMPOERNA TBK - Harditama, Rangga Rudvi; Utami, Elok Sri; Mufidah, Ana (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2015)
This study analyze about financial performance of the company with Dupont system. The object of the research is PT HM Sampoerna Tbk . PT HM Sampoerna Tbk is one of the leading cigarette manufacturer in Indonesia. The result of this research will be comparing with the industry average. From this research will be knowing the position of the company is below, same as or above of the industry average. The analysis technique used is du pont system and compared with the industry average, with the following steps: 1) Net Profit Margin (NPM), 2) Total Asset Turnover (TATO), 3) Return On Investment (ROI) . Key Words : Sistem Dupont, Net Profit Margin (NPM), Total Asset Turnover (TATO), Return On Investment